2017
DOI: 10.1111/cdoe.12325
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of oral health education on oral hygiene and dental caries in schoolchildren: Systematic review and meta‐analysis

Abstract: Traditional oral health educational actions were effective in reducing plaque, but not gingivitis. There is no long-term evidence in respect of the effectiveness of these interventions in preventing plaque accumulation, gingivitis and dental caries in the school environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
1
16

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 19 publications
4
109
1
16
Order By: Relevance
“…Over a period of 2 years, the caries prevalence increased from d1/d2 to d3 in as many as 20 children, followed by increment of new carious lesions in about all three groups with the least increment in study group followed by active and negative controls. This finding corroborates with the results of the systematic review and meta‐analysis stating the lack of evidence regarding the effectiveness of oral health education in reducing caries . They reported a lack of long‐term studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Over a period of 2 years, the caries prevalence increased from d1/d2 to d3 in as many as 20 children, followed by increment of new carious lesions in about all three groups with the least increment in study group followed by active and negative controls. This finding corroborates with the results of the systematic review and meta‐analysis stating the lack of evidence regarding the effectiveness of oral health education in reducing caries . They reported a lack of long‐term studies.…”
Section: Discussionsupporting
confidence: 89%
“…This finding corroborates with the results of the systematic review and meta-analysis stating the lack of evidence regarding the effectiveness of oral health education in reducing caries. 27 They reported a lack of long-term studies. Our study over the 2-year period found oral health education alone to be the least effective intervention to prevent ECC.…”
Section: Discussionmentioning
confidence: 99%
“…The search was conducted with the following search strategy: (“oral hygiene”[MeSH Terms] OR (“oral”[All Fields] AND “hygiene”[All Fields]) OR “oral hygiene”[All Fields]) AND (“dental caries”[MeSH Terms] OR (“dental”[All Fields] AND “caries”[All Fields]) OR “dental caries”[All Fields]) AND Clinical Trial[ptyp].” Titles, abstracts, full‐text papers and grant reports were screened for additional references. A two‐phase strategy was employed for the search that in a first phase included screening of titles and abstracts of the articles identified as potentially relevant during the electronic search, followed in a second phase by an assessment of the full‐text of articles deemed eligible for inclusion (eg, a systematic review). Reports in languages other than English were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The full list of the specific 8 173 reasons for exclusion of full texts is available in S3 Appendix. Figure 1 used meta-analysis to combine results [18][19][20][21][22][23][24][25][26][27][28], whereas the remaining nine SRs narratively 182 synthesized results [29][30][31][32][33][34][35][36][37]. Eleven SRs included studies located in countries with high-183 income or upper-middle income economies only [19,20,[23][24][25][29][30][31][32][33]37,38,39].…”
Section: Risk Of Biasmentioning
confidence: 99%